P022 Is intravaginal Boric acid an alternative therapeutic option for vaginal trichomoniasis?. (30th June 2016) - Thorley, Nicola; Ross, Jonathan
Abstract : Background/introduction: Current national guidance recommends treating Trichomonas vaginalis (TV) infection with nitro-imidazole therapy. The high prevalence of TV, high rate of metronidazole resistance and limited tolerability to nitroimidazoles when treating TV, suggest that alternative treatment regimens are required. Intravaginal Boric acid (BA) pessaries are available and have been used to safely treat vulvo-vaginal candidiasis and bacterial vaginosis. Aim(s)/objectives: We aimed to review the evidence for the safety and efficacy of BA for the treatment of TV. Methods: We performed a systematic review, in accordance with Centre for Reviews and Dissemination methods, of the evidence for the use of BA as a topical treatment for TV. Results: No randomised controlled trials or case series were found. Case reports provided in vivo evidence that BA safely and effectively treated TV. These cases, in the setting of resistant TV or severe metronidazole allergy, were managed with combination treatment administered over a period of 4 weeks to 5 months using doses of boric acid ranging from 600 mg once a day to 600 mg twice a day. No studies assessed the efficacy of BA in uncomplicated TV infection. In vitro, low concentrations (0.2%) of BA reduced the growth rate of TV, whereas higher concentrations (≥0.4%) were lethal to both laboratory TV strains and clinical isolates, providing evidence that the inhibitory effect of BA on TV is dose-dependent. Discussion/conclusion: BA is well-tolerated and has in vitro and in vivo activity against TV. There is limited evidence on the appropriate dosing schedule. There is need for further evaluation in a clinical trial.